Korupsi dalam Perspektif Alquran - Birahmat, Budi; Dedi, Syarial (STAIN Curup, 2018)
This article aims to track the Qur'an review of corruption. Because one of the most prevalent issues in Indonesia today is criminal acts of corruption, various ways have been done by the State to overcome corruption, from changing the law, establishing an institution specifically dealing with corruption to increase the sanction for convicted of corruption, but it is still not yet yielding results that encourage the community. The data presented in this paper is sourced from literature review by tracing the sources directly related to the theme especially the Qur'an and Sunnah. From the results of this study found that: Corruption as an extra-ordinary crimes crime is not explicitly mentioned by the Qur'an, but some terms such as ghulul, suht, sarq, hirabah some terms are considered to represent the Qur'an's notion of corruption. The punishment for the perpetrators of corruption, the most appropriate according to the authors is the punishment of the ta'dzir finger which in its implementation may equal or even exceed the sanction of hadd penalty. In this case the rulers are given the power to determine punishments according to the public interest, and should not be contrary to the provisions of shari'ah and general principles, such as applying Undang-undang No. 31 Tahun 1999 and which has been perfected by Undang-undang Nomor 20 Tahun 2001 Tentang Pemberantasan Tindak Pidana Korupsi.